2015
DOI: 10.3171/2015.3.spine14870
|View full text |Cite
|
Sign up to set email alerts
|

Intraspinal pressure and spinal cord perfusion pressure after spinal cord injury: an observational study

Abstract: OBJECT In contrast to intracranial pressure (ICP) in traumatic brain injury (TBI), intraspinal pressure (ISP) after traumatic spinal cord injury (TSCI) has not received the same attention in terms of waveform analysis. Based on a recently introduced technique for continuous monitoring of ISP, here the morphological characteristics of ISP are observationally described. It was hypothesized that the waveform analysis method used to assess ICP could be similarly applied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 26 publications
1
48
0
1
Order By: Relevance
“…Therefore, not only hypoperfusion (SCPP below 90 mmHg), but also hyperperfusion (SCPP above 100 mmHg) may be detrimental for the injured spinal cord. This is consistent with our earlier report of a U-shaped relationship between the spinal pressure reactivity index and SCPP, which also indicated optimum SCPP around 90 mmHg 5,8,21 . After TSCI, ISP is 20 -30 mmHg and therefore SCPP 90 -100 mmHg corresponds to mean arterial pressure 110 -130 mmHg.…”
Section: Annals Of Neurologysupporting
confidence: 93%
See 1 more Smart Citation
“…Therefore, not only hypoperfusion (SCPP below 90 mmHg), but also hyperperfusion (SCPP above 100 mmHg) may be detrimental for the injured spinal cord. This is consistent with our earlier report of a U-shaped relationship between the spinal pressure reactivity index and SCPP, which also indicated optimum SCPP around 90 mmHg 5,8,21 . After TSCI, ISP is 20 -30 mmHg and therefore SCPP 90 -100 mmHg corresponds to mean arterial pressure 110 -130 mmHg.…”
Section: Annals Of Neurologysupporting
confidence: 93%
“…We also showed that simultaneous monitoring of SCPP and microdialysis could be used to enhance drug entry at the injury site. Based on our current findings and earlier studies [4][5][6][7][8][9]20,21 , a large-scale study of outcome from TSCI in patients who have monitoring vs. those who do not is warranted.…”
Section: Annals Of Neurologymentioning
confidence: 59%
“…20 Currently, ICP monitoring and CPP optimization are the standard of care when managing severe TBI patients in developed countries. Based on our earlier studies 19,20,24,26 and the safety profile of ISP monitoring shown here, we hope that our ISP monitoring technique is used by other centers. Ultimately, a randomized controlled trial is warranted to determine if ISP monitoring and SCPP optimization improve outcome after TSCI.…”
Section: Discussionmentioning
confidence: 92%
“…26 Our analysis shows that the ISP and SCPP waveforms after TSCI have similar characteristics as the ISP and CPP waveforms after TBI, respectively. 24 We, therefore, proposed that the concepts of pressure reactivity (quantified using PRx), optimum cerebral perfusion pressure (CPP opt ), and compensatory reserve (quantified using RAP), which had been developed for TBI, could also be applied to the damaged spinal cord to yield spinal pressure reactivity (sPRx), optimum spinal cord perfusion pressure (SCPP opt ), and spinal compensatory reserve (sRAP). After TSCI, bony decompression (i.e., realignment of the fracture and laminectomy) does not effectively reduce the elevated ISP at the injury site.…”
mentioning
confidence: 99%
“…This treatment paradigm has resulted in a significant reduction of mortality and morbidity associated with TBI and is attributed to the significant improvements in clinical outcomes for these patients [Marshall et al, 1979;Miller et al, 1981]. A few recent studies have suggested that increases in tissue pressure after SCI are associated with negative functional outcomes Varsos et al, 2015] ( fig. 1 a), and surgical alleviation of this pressure improves functional outcomes in both experimental animals [Yang et al, 2013] as well as patients .…”
Section: Pressure-induced Damage To the Spinal Cord After The Primarymentioning
confidence: 99%